The in Vitro Effects of Mithramycin on the Aggregation and the Calcium Uptake of Human Platelets - Chao, Francis C.; Tullis, James L. (Thrombosis and Haemostasis, 1973)
The in vitro incubation of platelets with mithramycin caused a biphasic effect on ADP-induced aggregation. At a low dose of 10 [xg/ml, mithramycin caused an enhancement of aggregation whereas at high doses above 50 [μg/ml, it produced variable effects on aggregation with inhibition predominating. Effects on ADP-induced aggregation similar to those caused by mithramycin were produced by the simple addition of CaCl2 solution to the plasma medium. Mithramycin in the range which increased aggregation altered neither the whole blood clotting times nor the ionic calcium concentrations, but did increase the uptake of radioactive calcium by platelets. The results confirmed the in vivo observations that mithramycin treatment during tumor chemotherapy may directly alter the aggregation response of circulating platelets to ADP. The effects of mithramycin on aggregation may be mediated by alteration of calcium influx in normal platelets.